Communication Ability, Work Attitude, Compensation, and Commitment to Performance of Service Employees Labuhanbatu District Transportation - Andre Syafrizal; Yuniman Zebua; Bayu Eko Broto (Quantitative Economics and Management Studies, 2022)
Human resources are the most important investment so that This study aims to analyze communication skills, compensation work attitudes and commitment to the performance of the Labuhanbatu Regency Transportation Service employees. This type of research is quantitative, the place of this research is the Department of Transportation of Labuhanbatu Regency. In this study, the population is the employees of the Labuhanbatu Regency Transportation Service as many as 84 people . The sampling technique used is saturated sampling. Saturated sampling technique is a sampling technique when all members of the population are used as samples. Due to the number of employees of the Labuhanbatu Regency Transportation Service as many as 84 people (less than 100 people), then all employees were taken as objects of research. The analysis used is multiple linear regression. Observation, documentation and questionnaires using a Likert scale is a data collection technique used in this study. The results of the regression analysis obtained the t-count value of 3.875 > t-table 1.6643, Then the results of the regression analysis obtained the t-count value of 2.135 > t-table 1.6643, obtained the t-count value of 2.322 > t-table 1.6643 and then the t-count value of 4.414 > t table 1.6643. In this case, it means that each variable of communication ability (X 1 ), work attitude (X 2 ), compensation (X 3 ) and commitment (X 4 ) has a positive effect on the employee performance variable (Y). The calculated F value is 52.503> F table 2.49 with a significance value of 0.000 <0.05. From these results, it can be concluded that communication (X 1 ), work attitude (X 2 ), compensation (X 3 ) and commitment (X 4 ) simultaneously have a positive and significant effect on employee performance (Y). R Square value of analysis of the coefficient of determination of 0.727 means that employee performance can be explained by the variables of communication skills (X 1 ), work attitude (X 2 ), compensation (X 3 ) and commitment (X 4 ) of 72.7%, while the remaining 27.3% can be explained by other variables not examined in this study.